Internal and External Security Challenges of Nepal - Karki, Sumitra (Unity Journal, 2021)
Nepal has been a home to diversified settlement in terms of ethnicity, religion, dialect and culture since its outset in civilization. It also lies between two great military and economic giants of Asia – India and China – that are hostile to each other. While these bring abundant opportunities for Nepal, it possesses several internal and external security threats. Nepal suffers from cyber-attack, environmental degradation, pandemic, ethnic, racial or religious conflicts, inequality and poverty, extremism, human trafficking, corruption, migration and trans-boundary crime. In addition, Nepal also faces several security threats, traditional and non–traditional, including terrorism and insurgency. These threats possess serious implications on peace and security of Nepal and the South Asian region. There is a need of serious study about the major internal and external security challenges that Nepal faces in recent decades. This study aims at examining some of the major security challenges, explore the factors behind it, and attempt to suggest few policy recommendations to the government of Nepal to deal with them. The study is conducted by reviewing the primary and secondary sources of data. The primary data includes documents of the government agencies, press release, joint statement and organizational reports. It also includes the interviews with security experts, bureaucrats, policy makers and academicians. Similarly, secondary data includes books, news reports, academic journals, seminars report and reports of research institutes and think tanks. The study highlights that Nepal should prepare itself to meet with the emerging internal and external security challenges what have emerged in recent times. With the rise of India and China, two adversarial powers in the region, Nepal possess extreme challenges in days to come. Similarly, hardly any countries of the world had prepared itself to deal with recent pandemic like COVID-19 that has shattered even the most powerful countries of the world. Taking lessons from these, it is time for Nepal to learn and prepare to mitigate the challenges.